Analisis Stabilitas Lereng Disposal Menggunakan Metode Bishop, Janbu, dan Ordinary - Daniel Pasole; John Patanduk; Irwan Lie Keng Wong (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
The stability of disposal or stockpiling slopes in open mines at PT. Vale Indonesia Tbk has become a problem that requires more attention to the continuity of mining activities and is an important matter for conducting technical studies. Factors that often result in collapse or landslide are viewed from the influence of slope geometry such as the inclination angle of the embankment and the composition of the material layer as well as due to the load acting on the crest of the disposal slope. The purpose of this study is to determine whether a slope is stable or not, which is displayed in the form of the value of the safety factor. The stages of the slope stability analysis process were carried out using three methods, namely Bishop, Janbu, and Ordinary which in the analysis process used the Geoslope/W 2012 software. The parameters used were the internal shear angle, cohesion, and soil density. Where the safety factor is obtained from three methods, namely before the change, the results of slope analysis can be seen that the safety factor of the slope using the Geoslope/W 2012 software is in unsafe conditions. While the results of the slope stability analysis by changing the geometry of the slope and the arrangement of the material layers due to the load at the crest/peak of the slope, which changes the slope angle from 35 ° to 25 ° and changing the layer of material composition can increase slope stability, the safety factor obtained by every three methods namely, Janbu, 1,763; Bishop 1608 and Ordinary 1,758.